Authoritarian Parenting in Shaping the Characteristics of Ruth Young in Amy Tan’s The Bonesetter’s Daughter - Lengari, Clara Acitya Ose; Widyastuti, Dewi (Universitas Sanata Dharma, 2018)
This undergraduate study discusses The Bonesetter’s Daughter, a novel which was written by Amy Tan. It tells about the life of a mother, Luling Young, and her daughter, Ruth Young. This study focuses on Luling and Ruth in their past and present conditions. Throughout Ruth’s life, Luling practiced an authoritarian parenting style which appealed to the researcher to analyze the cause and effect of Luling’s parenting style in shaping Ruth’s characteristics and behaviors. Two problems were formulated to limit the study. The objectives of this research are to answer: (1) how Luling Young showed the authoritarian parenting in the novel, and (2) how the authoritarian parenting shaped Ruth Young’s characteristics. The first analysis of the study shows that as an authoritarian parent, Luling Young is low on affection, high on behavioral control and high on psychological control. Luling rarely communicates well and shows physical affections towards Ruth. She is also highly demanding and controlling in Ruth’s life. Besides, she is quick-tempered over small problems and sometimes shows love withdrawal. Those acts of authoritarian parenting style influence Ruth’s characteristics. The first effect is Ruth’s internalizing behaviors. Due to the combination of Luling’s low affection and high psychological control, Ruth has anxiety, is fearful, suicidal and skeptical of her mother. Those are happened because the restriction and oppression which are given by Luling affect Ruth’s mental state. The second outcome is Ruth’s externalizing behaviors which come from a combination of high behavioral control and high psychological control. Ruth becomes hesitant in talk, explosive-tempered and suicidal. Therefore, Luling Young’s practice of an authoritarian parenting influences the characteristics-shaping of Ruth Young.Keywords: authoritarian parenting, characteristic shaping